2004
DOI: 10.4049/jimmunol.172.4.2487
|View full text |Cite
|
Sign up to set email alerts
|

Protective T Cell Immunity against Malaria Liver Stage after Vaccination with Live Sporozoites under Chloroquine Treatment

Abstract: In this study we present the first systematic analysis of the immunity induced by normal Plasmodium yoelii sporozoites in mice. Immunization with sporozoites, which was conducted under chloroquine treatment to minimize the influence of blood stage parasites, induced a strong protection against a subsequent sporozoite and, to a lesser extent, against infected RBC challenges. The protection induced by this immunization protocol proved to be very effective. Induction of this protective immunity depended on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(294 citation statements)
references
References 40 publications
(33 reference statements)
12
281
1
Order By: Relevance
“…Although it is reported that VACV intermediate antigens are preferentially recognized by CD4 T-cells (Yang et al, 2011b), we demonstrate that the early LACK expression driven by the early promoter of MVA-LEO160-LACK can positively influence LACK-specific CD4 T-cell responses. While antigen-specific T-cell responses can provide protective immunity against parasites (Belnoue et al, 2004), in a Leishmania infection model, only CD4 T-cell immunogenicity correlated with this protection (Darrah et al, 2007). Following Leishmania major infection, BALB/c mice show principally a Th2 response, due to the Th2 immunogenicity of the LACK antigen (Mougneau et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is reported that VACV intermediate antigens are preferentially recognized by CD4 T-cells (Yang et al, 2011b), we demonstrate that the early LACK expression driven by the early promoter of MVA-LEO160-LACK can positively influence LACK-specific CD4 T-cell responses. While antigen-specific T-cell responses can provide protective immunity against parasites (Belnoue et al, 2004), in a Leishmania infection model, only CD4 T-cell immunogenicity correlated with this protection (Darrah et al, 2007). Following Leishmania major infection, BALB/c mice show principally a Th2 response, due to the Th2 immunogenicity of the LACK antigen (Mougneau et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest an important role for non-CSP responses as well. Mouse studies suggest that fewer CPS parasites and fewer CPS immunizations are required for protection compared with the RAS regimen (26). Similarly, a single CPS immunization via the bites of 12-15 P. falciparum NF54-infected mosquitoes protected 4 of 10 human subjects from developing detectable blood-stage parasitemia following a second CPS immunization and reduced the peak parasitemia >20-fold in the remaining infected individuals (5).…”
Section: Discussionmentioning
confidence: 99%
“…Single immunization using CPS or late-arresting GAP approaches usually provides greater protection than an equivalent number of RAS parasites (11,26). RAS parasites arrest shortly after hepatocyte infection, whereas GAPs progress further depending on the specific genetic lesion.…”
mentioning
confidence: 99%
“…Efficient induction of sterile protection against malaria can be achieved in rodents by inoculation of intact sporozoites under chemoprophylaxis (Belnoue et al, 2004;Borrmann & Matuschewski, 2011). In an analogous proof-of-concept CHMI study, malaria-naïve adult volunteers received 12-15 P. falciparum-infected mosquito-bites once a month for 3 months under chloroquine prophylaxis.…”
Section: Protection By Controlled Human Malaria Infections Under Chemmentioning
confidence: 99%